2022
DOI: 10.1021/acs.orglett.2c02714
|View full text |Cite
|
Sign up to set email alerts
|

On-DNA Synthesis of Functionalized 4H-Pyran Scaffolds for Focused DNA-Encoded Chemical Libraries

Abstract: The functionalized 4H-pyran scaffold has aroused synthetic attention because it is widely found in many interesting pharmacologically relevant compounds. We here disclose its incorporation into DNA-encoded chemical libraries, combining this scaffold with the merits of scaffold architecture in drug design. Under the optimized DNA-compatible conditions, functionalized 4H-pyrans were efficiently formed with a broad substrate scope. Among the 4Hpyrans formed, the axial structure features rotational restriction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…As well, a capped substrate with no expected reactivity was subjected to the typical coupling conditions as a control experiment, and the results demonstrated that the DNA oligo conjugate remained intact throughout the reaction process, thereby further verifying the DNA oligos' integrity (see SI S212−S223 for details). 17 In conclusion, we have developed a robust approach for the on-DNA formation of benzofurans from on-DNA aldehyde conjugates. The synthesis, featuring a sequential Seyferth− Gilbert homologation using an Ohira−Bestmann reagent, and a one-pot Sonogoshira coupling/heterocyclization can be conducted under mild reaction conditions and high conversions while tolerating a wide array of functional groups.…”
mentioning
confidence: 99%
“…As well, a capped substrate with no expected reactivity was subjected to the typical coupling conditions as a control experiment, and the results demonstrated that the DNA oligo conjugate remained intact throughout the reaction process, thereby further verifying the DNA oligos' integrity (see SI S212−S223 for details). 17 In conclusion, we have developed a robust approach for the on-DNA formation of benzofurans from on-DNA aldehyde conjugates. The synthesis, featuring a sequential Seyferth− Gilbert homologation using an Ohira−Bestmann reagent, and a one-pot Sonogoshira coupling/heterocyclization can be conducted under mild reaction conditions and high conversions while tolerating a wide array of functional groups.…”
mentioning
confidence: 99%
“…Moreover, the complexity of setups was minimized due to this open-air and catalyst-free condition. Besides, building blocks bearing an additional handle were investigated for diversification, 14 shown by the DNA-conjugated b1c5 product bearing a carboxylic acid group (see section 5 in Supporting Information).…”
mentioning
confidence: 99%
“…[26][27][28][29][30] Numerous reaction toolkits, which must be DNA-compatible, have been thereby developed and employed to construct encoded libraries, and the building blocks (BBs) for library construction should be conveniently accessible or commercially available to expand the chemical diversities to more complicated molecular architectures beyond encoding early-stage peptide-like libraries. [31][32][33] Therefore, there is an imminent need for incorporation of NPs with rich chemical diversities into DELs.…”
mentioning
confidence: 99%